Rett syndrome: a pediatric neurodevelopmental disorder - Van Acker, Richard (Henry Stewart Talks, 2010)
Prevalence of Rett syndrome, History of the disorder, Clinical presentation, Different stages of the syndrome, Diagnosis, IRSA diagnostic criteria, Necessary, supportive and exclusionary criteria, Diagnostic criteria associated features and disorders, IRSA vs. DSM-IV-TR, Atypical Rett syndrome, Differential diagnosis, Etiology of Rett syndrome, Random inactivation of one X-chromosome in each cell, Rett syndrome and sporadic mutation, Familial RTT, Rett syndrome and MECP2, Other genes associated with RTT, Mouse models, Neuropathology, Neuroanatomy, Neurochemical alterations in Rett syndrome, Growth patterns and nutrition, Cognitive and adaptive functioning, Communication, Orthopedic aspects and intervention, Hand stereotypes, Educational implications
Reviewed at 2020/11/09